Written Culture in a Colonial Context Africa and the Americas 1500-1900 - Delmas, Adrien (UCT Press, 2011)
There is very little in the modern literature on the history of written culture that describes the specific practices related to writing that were anchored in colonial contexts. It was not just ships, soldiers, missionaries and settlers that drove the process of European expansion from the 16th to the 19th centuries. The circulation of images, manuscripts and books between different continents played a key role too. The introduction and appropriation of writing into societies without alphabets was a major factor in changing the very function and meaning of written culture. This book explores the extent to which the types of written information that resulted during colonial expansion shaped the numerous and complex processes of cultural exchange from the 16th century onwards in Africa and the Americas.